Morphological Analysis of Activity-Reduced Adult-Born Neurons in the Mouse Olfactory Bulb - Dahlen, Jeffrey E.; Jimenez, Daniel A.; Gerkin, Richard C.; Urban, Nathan N. (Frontiers in Neuroscience, 2011)
Adult born neurons are added to the olfactory bulb (OB) throughout life in rodents. While many factors have been identified as regulating the survival and integration of adult-born neurons (ABNs) into existing circuitry, the understanding of how these factors affect ABN morphology and connectivity is limited. Here we compare how cell intrinsic (siRNA knock down of voltage gated sodium channels NaV1.1-1.3) and circuit level (naris occlusion) reductions in activity affect ABN morphology during integration into the OB. We found that both manipulations reduce the number of dendritic spines (and thus likely the number of reciprocal synaptic connections) formed with the surrounding circuitry and inhibited dendritic ramification of ABNs. Further, we identified regions of ABN apical dendrites where the largest and most significant decreases occur following siRNA knock down or naris occlusion. In siRNA knock down cells, reduction of spines is observed in proximal regions of the apical dendrite. This suggests that distal regions of the dendrite may remain active independent of NaV1.1-1.3 channel expression, perhaps facilitated by activation of T-type calcium channels and NMDA receptors. By contrast, circuit level reduction of activity by naris occlusion resulted in a global depression of spine number. Together, these results indicate that ABNs retain the ability to develop their typical overall morphological features regardless of experienced activity, and activity modulates the number and location of formed connections.